2018
DOI: 10.3390/nano8060394
|View full text |Cite
|
Sign up to set email alerts
|

Nanoporous Ni with High Surface Area for Potential Hydrogen Storage Application

Abstract: Nanoporous metals with considerable specific surface areas and hierarchical pore structures exhibit promising applications in the field of hydrogen storage, electrocatalysis, and fuel cells. In this manuscript, a facile method is demonstrated for fabricating nanoporous Ni with a high surface area by using SiO2 aerogel as a template, i.e., electroless plating of Ni into an SiO2 aerogel template followed by removal of the template at moderate conditions. The effects of the prepared conditions, including the elec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(4 citation statements)
references
References 34 publications
0
4
0
Order By: Relevance
“…CoFe 2 O 4 NPs are attracted to magnetic fields and generate heat when they move; this magnetic fluid hyperthermia is central to these noninvasive cancer treatments [ 73 ]. Similarly, nickel (Ni) NP have a high surface area relative to their size, allowing for a large capacity of drugs to be carried in the drug delivery system, imaging, and cancer treatment [ 74 ].…”
Section: Important Np Physical Compositionsmentioning
confidence: 99%
“…CoFe 2 O 4 NPs are attracted to magnetic fields and generate heat when they move; this magnetic fluid hyperthermia is central to these noninvasive cancer treatments [ 73 ]. Similarly, nickel (Ni) NP have a high surface area relative to their size, allowing for a large capacity of drugs to be carried in the drug delivery system, imaging, and cancer treatment [ 74 ].…”
Section: Important Np Physical Compositionsmentioning
confidence: 99%
“…Experiments showed that the adsorptiondesorption process is reversible, and the amount of adsorbed hydrogen is relatively low (about 3 wt%) [12,21,23,54]. Carbon nanostructures and other nanoporous materials have also been examined for hydrogen storage [23,25,[55][56][57][58]. It is found that the amount of absorbed hydrogen, which is very low, increased with temperature and pressure, indicating that the mechanism of storing is of a chemical reaction nature, preferably physisorption.…”
Section: Introductionmentioning
confidence: 99%
“…During the progress, CS was used as a carbon and nitrogen source and F127 as the template. This result shows that the application performance of prepared MCM depended mainly on the morphology and pore structure characteristics (surface area, total pore volume and pore size distribution), which related to macroscopic reaction factors (or preparation conditions) such as raw material ratio, reaction temperature, reaction time, prepolymer drying and carbonization conditions [12][13][14][15][16][17][18][19][20][21][22][23]. Some researchers believe that hydrogen bonding is the driving force of the reaction between CS and F127 [24][25][26].…”
Section: Introductionmentioning
confidence: 99%